2014
DOI: 10.1021/jp501608b
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic Resonance in Electron Transfer Oscillations of Extended Viologen

Abstract: Selective generation of only odd harmonics and the absence of even harmonics were never described for electrochemical oscillators though this phenomenon is known in special fields of physics and in biological systems. The heterogeneous electron transfer to the extended viologen with four repetitive viologen units yields electrochemical current oscillations. Small perturbation of the applied voltage by only a few millivolts sine wave results in current oscillations, which selectively enhance only the odd harmon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…We described an important role of radical intermediates in our previous studies of oscillating heterogeneous redox systems. Quaternary N -heterocyclic systems yielded oscillations, period doubling and transfer to the deterministic chaos on the basis of cationic catalysis or multielectronic transfers. The present current instability is less intensive nevertheless it is quite distinct. Application of analysis of the system dynamics can confirm or disprove the irregularities as purely random events or deterministic fluctuations .…”
Section: Resultsmentioning
confidence: 87%
“…We described an important role of radical intermediates in our previous studies of oscillating heterogeneous redox systems. Quaternary N -heterocyclic systems yielded oscillations, period doubling and transfer to the deterministic chaos on the basis of cationic catalysis or multielectronic transfers. The present current instability is less intensive nevertheless it is quite distinct. Application of analysis of the system dynamics can confirm or disprove the irregularities as purely random events or deterministic fluctuations .…”
Section: Resultsmentioning
confidence: 87%
“…[28] Examples include pulsing Belousov-Zhabotinsky reactions, [29] as well as electron transfer reactions. [30] In particular, stochastic resonance plays a role in biochemical reactions, such as cell signaling, where noise due to a small number of signaling molecules can control gene silencing. [31][32] …”
Section: Discussionmentioning
confidence: 99%
“…This effect is generally observed near unstable points of the reaction's state space as a function of perturbation parameters . Examples include pulsing Belousov‐Zhabotinsky reactions, as well as electron transfer reactions . In particular, stochastic resonance plays a role in biochemical reactions that are part of feedback cycles, such as cell signaling, where noise due to a small number of signaling molecules can control gene silencing …”
Section: Discussionmentioning
confidence: 99%
“…At high BP concentration two radical cations form a dication dimer, which can be further reduced. A decrease in temperature favors the dimer formation. In addition to a σ-type of dimer the formation of an association-type of dimer was postulated, and several different association patterns have been proposed for such dimers. ,, The ability of BP to participate in the comproportionation/disproportionation equilibria and other follow-up chemical reactions is essential for the observation of stochastic resonance and oscillatory phenomena in the extended viologen molecules with multiple redox centers. , …”
Section: Introductionmentioning
confidence: 99%
“…While in the first case the spin density of the corresponding radical cation is delocalized over the bipyridine backbone resulting in no follow-up reaction, in the second case we will report here a completely different behavior. Previously, it has been shown that A 2+ accepts reversibly four electrons and serves as a building block for longer oligomers with interesting electron transfer properties. ,,, Proper understanding of the electron transfer mechanism in this simple structure will help us understand more complicated phenomena such as switching of the single-molecule conductance mechanism from superexchange to hopping, negative differential resistance, and current oscillations in a series of oligomers containing repeated motifs of A 2+ .…”
Section: Introductionmentioning
confidence: 99%